Análisis de los servicios turísticos categorizados por el Ministerio de Turismo en la Ruta del Rio del cantón Quevedo, año 2021 - Rivera Arteaga, Lidia Paola (2021)
The Cantón Quevedo is a tourist city located on the Ecuadorian coast of the province of Los Ríos, Quevedo provides a deep cultural and artistic feeling in the streets we can remember anecdotes of what it was like to live the past, its legends and its customs that will always be present. “Ruta del Río”, built by the municipality in agreement with the Los Ríos Prefecture, generates many fundamental aspects for the city. Currently there is a project that is being developed and the purpose of which is to provide free land to entrepreneurs through a loan so that they can build and install their tourist businesses. The undertakings must be for accommodation, food, beverages, tourist operations, gyms and sports. Taking into account that the requirements are that the entrepreneur present his tourism project and that he has the budget for its execution. Building standards must be rustic and environmentally friendly. Tourism activities are linked to the tourism promotion of the same, in Ecuador the Ministry of Tourism is the regulatory body that promotes national tourism activities with potential and access for international tourists, this research project seeks to analyze tourism services to generate a Social and economic radiography of the activities to be carried out on the “Ruta Del Rio”, its development and points to improve to attract internal and external tourists.